Paradoxical articular manifestations in patients with inflammatory bowel diseases treated with infliximab. Issue 8 (August 2016) - Thiebault, Henri; Boyard-Lasselin, Pauline; Guignant, Caroline; Guillaume, Nicolas; Wacrenier, Adrien; Sabbagh, Charles; Rebibo, Lionel; Brazier, Franck; Meynier, Jonathan; Nguyen-Khac, Eric; Dupas, Jean-Louis; Goëb, Vincent; et al.
Abstract : Introduction: Articular involvement is the most common extraintestinal manifestation associated with inflammatory bowel diseases (IBDs). Manifestations are 'paradoxical' when they occur during treatment, notably with anti-tumor necrosis factor (anti-TNF) drugs, which are expected to prevent or treat them. The aim of this study was to assess the frequency, characteristics, and associated factors of paradoxical articular manifestations in patients with IBD treated with anti-TNF. Patients and methods: In this prospective single-center study, an examination by a rheumatologist was systematically offered to all patients with IBD treated with infliximab (IFX) to assess the prevalence of articular manifestations and distinguish between those related to treatment and those associated with intestinal disease. Paradoxical manifestations were defined as the occurrence of articular manifestations (excluding induced lupus and hypersensitivity reactions) during anti-TNF therapy in patients with intestinal remission. Measures of biological inflammatory, immunological markers, HLA-B27 allele, IFX trough levels, and anti-IFX antibody (Ab) were performed for all patients. Results: Between May 2013 and April 2014, 65 patients with Crohn's disease and 15 with patients ulcerative colitis treated with IFX were included. The median duration of anti-TNF therapy was 66 months [quartile (Q)1=23 months–Q3=81 months]. Articular manifestations were observed in 50 (62%) patients treated with IFX. Eleven percent ( n =9) were considered to be associated with IBD and 16% ( n =13) to be associated with anti-TNF therapy. Among articular manifestations associated with anti-TNF therapy, nine (11%) patients were considered paradoxical, two (2%) as drug-induced lupus, and two (2%) as a hypersensitivity reaction. Among the nine patients with paradoxical manifestations, all had Crohn's disease in clinical remission, three patients presented a spondyloarthropathy, and three developed associated paradoxical psoriasis. No patient discontinued anti-TNF because of the articular manifestations. Methotrexate was effective on articular symptoms in two of the three treated patients with paradoxical manifestations. No clinical or biological factors, including IFX trough levels, were associated with the occurrence of paradoxical manifestations. Conclusion: Paradoxical articular manifestations in IBD patients treated by anti-TNF are common, affecting more than 10% of patients. These events are generally mild and do not need discontinuation of anti-TNF therapy.